Exploring the transmission mechanism of self discrepancy on perceived academic stress–based on the methods of posting grades ranking - Shunxu Peng; Feng Yi (PLoS ONE, 2025)
Academic stress is one of the most significant factors affecting adolescents’ mental health. Various methods of posting grades ranking may lead to students to perceive different levels of psychological stress, which in turn impacts the development of their mental health. Using Propensity Score Matching and Ordered Probit methods with educational quality monitoring data of 5405 eighth-grade students from 39 schools in District F, this paper examines the impact of posting grades ranking on students’ perceived academic stress in mathematics. It also explores the potential mechanisms and heterogeneous results of this impact, and concludes that: first, self-discrepancy induced by differences on posting grades ranking methods increases students’ perceived academic stress, with a higher degree of self- discrepancy leads to greater academic stress to some extent; second, academic stress induced by differences on posting grades ranking methods has a significant impact only on female students, county and rural students, and medium performance group students; third, self-discrepancy contributes to academic stress through the mediating pathway of academic emotions. This study can offer practical insights for recommendations for the implementation of the “Double-Reduction” policy.